INTERNAL CONTROL SYSTEM AS A MEANS OF PREVENTING FRAUD IN FINANCIAL INSTITUTION IN NIGERIA (Journal of Global Accounting, 2024)
This study was carried out with the aim of appraising internal control as means of preventing fraud. In order to actualize the objectives of the study, various literature and theoretical issues were discussed. The instrument used for the purpose of this research was gathered through primary and secondary sources. The primary source is through questionnaires while the secondary source extracts from textbooks by different authors, journals and other publications. The mass of information generated from the questionnaires was summarized in form of table and analyzed using simple percentage. The researcher administered two hundred (200) questionnaires to respondents, out of which one hundred and sixty (160) were retrieved for the purpose of presenting and analyzing responses to issues raise in the questionnaires. The data collected was analyzed using Z-test statistical tool. The findings from analysis revealed among other things that, lack of a good internal control is a major cause of fraud in financial institution. We therefore recommend that management of every bank should create and establish a standard internal control system, strong enough to stand against the wiles of fraud in order to promote continuity of operations and to ensure the liquidity or solvency and going concern concept of the banks
Keywords: Financial Institutions; Fraud, Prevention; Internal Control System